Nenhuma vontade do povo: o Rio Grande do Sul na guerra contra o Uruguai e o Paraguai (1863-1870) - Jardim, Wagner Cardoso (2020)
Between 1863 and 1870, the then province of Rio Grande do Sul was directly involved in the resumption of the bellicose status in the platinum region. The onslaught of sectors of farmers, cattle raisers and beef jerky producers located in southern Rio Grande do Sul and northern Uruguay against the statist policies of the white government of Bernardo Berro and later Atanásio Cruz Aguirre were in line with the intention of Venancio Flores, eastern leader, linked to Argentine president Bartolomé Miter, of retaking power in Uruguay. From a very early age, in this dispute between the Orientals, farmers from Rio Grande do Sul armed hundreds of men in support of Flores. Before long, the new imperial government, in the hands of the Liberal Party, resumed its assault on the platinum region. They wanted to guarantee, once and for all, the limits with Paraguay, which had been suspended for some time. Thus, an atmosphere of war was created. This war materialized with the frustrated Uruguayan submission through diplomatic channels and invasion of that country, without a declaration of war, with a strong military apparatus, in support of Venancio Flores. With that, the imperial government attracted the much desired parallel war with the Paraguayan government. The province of Rio Grande do Sul was initially thought of as a base of operations against Paraguay and the main imperial military bastion. Once the issue in Uruguay was finished, with the effective participation of land forces sent from the Rio Grande do Sul borders, the invasion of Paraguay was prepared. This would not happen due to Paraguay's entry into southern territory. The province's defense forces, led by the most experienced military leaders, were insufficient. The Paraguayans stayed for almost two months. Surrendered in Uruguaiana, the war would continue in Paraguayan territory. Rio Grande do Sul maintained its importance. It was the province that sent more men to the conflict, in proportion to the number of inhabitants. Life in the province, in this period in which the conflict lasted, would be profoundly altered. Thousands of men arriving, camping and marching through the province. Hundreds would die of illnesses before they even crossed the border. Forced recruitment; by consensus; in substitution or volunteering. Through the farms and villages, those who hid from the agents of the recruitment or deserters. The hands that held the rifle released the hoes. Thousands of men were pulled out of their business to fight a war that did not concern them. Meanwhile, sectors of Rio Grande's owning class that provoked and encouraged the war did not fight it. This research aimed to broadly analyze the direct and indirect implications of the Triple Alliance War against Paraguay for Rio Grande do Sul.